Identifikasi Bahaya dan Penilaian Risiko Pengujian Conveyor Belt di Laboratorium PT. X Menggunakan Metode Hazard Identification and Risk Assessment - ., khamaludin; Sumarno, Dodi Iwan (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
In an effort to ensure the quality of conveyor belt products at PT. X, before being sent to consumers, product testing needs to be done. The conveyor belt testing activity has the potential for work accidents to be experienced by the testing operator. To anticipate this, it is necessary to identify hazards and assess risks to Occupational Safety and Health (K3) from all conveyor belt testing activities. The scope of this research is only on conveyor belt testing activities in the testing laboratory section of PT. X. The method used in this Hazard Identification and Risk Assessment is by using the Hazard Identification and Risk Assessment (HIRA) method, namely by determining all types of testing activities, their hazards and risks and determining the severity, probability of occurrence, controls carried out, and level of concern. Test operators are sufficiently concerned about the importance of risk hazard control and all testing activities are equipped with controls in the form of the use of Personal Protective Equipment and engineering controls. There are 16 types of hazardz and 12 risks in coveyor belt testing activities. The IBPR value of all conveyor belt testing activities is no more than zero or there is no significant hazard.